OC-033 The Tweak And Fn14 Pathway As Potential Mediator Of Liver Fibrosis. (9th June 2014) - Wilhelm, A; Munir, M; Humphreys, E; Adams, D; Burkly, L; Afford, S; Weston, C
Abstract : Introduction: The TNF superfamily ligand TWEAK and its cognate receptor Fn14 have been implicated in the pathogenesis of liver disease and have been predominantly associated with liver progenitor cell proliferation and ductular reaction. We hypothesised that TWEAK and Fn14 may also be involved in the establishment and progression of fibrosis via a direct effect on hepatic stellate cell (HSC) function. Methods: TWEAK and Fn14 expression was studied by qPCR, western blot and immunostaining in tissue and stromal cells from explanted human liver specimens and normal donor livers surplus to surgical requirements, or as a byproduct of surgical resection. The responses of HSCs to TWEAK were investigated by western blot, live cell imaging and proliferation assays. TWEAK was measured in HSC supernatant by ELISA. Results: Confocal microscopy revealed localisation of Fn14 to cells expressing stromal markers in normal human livers, with significant upregulation in diseased livers. Fn14 expression was confirmed in both primary human HSCs and myofibroblasts in vitro . Stimulation with recombinant TWEAK led to an upregulation of NF-kB signalling and induced proliferation in cultured HSCs. TWEAK immunostaining localised the protein to the fibrotic areas of ALD and NASH liver sections suggestive of an autocrine regulation of Fn14 signalling. We confirmed that HSCs express TWEAK and release it into their environment by qPCR and ELISA, and demonstrated that function-blocking TWEAK antibodies reduced the proliferative capacity of HSC. Conclusion: Our study suggests that TWEAK/Fn14 promotes liver fibrosis via enhanced proliferation of HSC, possibly through an autocrine mechanism driven by HSC production of TWEAK. Disclosure of Interest: None Declared.